Love marriage ebook A novel. - Ali, Monica (2022)
Named a Best Book of 2022 So Far by The New Yorker ! "Cultural clashes, political satire, Oedipal conflicts, elegant prose—they're all here in this romp of a book." —Oprah Daily A Phenomenal Book Club Pick and a New York Times Book Review Group Text Selection, Love Marriage is a glorious moving novel from Booker Prize shortlisted Monica Ali, who has "an inborn generosity that cannot be learned" ( The New York Times Book Review) . In present-day London, Yasmin Ghorami is twenty-six, in training to be a doctor (like her Indian-born father), and engaged to the charismatic, upper-class Joe Sangster, whose formidable mother, Harriet, is a famous feminist. The gulf between families is vast. So, too, is the gulf in sexual experience between Yasmin and Joe. As the wedding day draws near, misunderstandings, infidelities, and long-held secrets upend both Yasmin's relationship and that of her parents, a "love marriage," according to the family lore that Yasmin has believed all her life. A gloriously acute observer of class, sexual mores, and the mysteries of the human heart, Monica Ali has written a "riveting" ( BookPage , starred review) social comedy and a moving, revelatory story of two cultures, two families, and two people trying to understand one another that's "sure to please Ali's fans and win some new ones" ( Publishers Weekly ).